The Effect of Bajakah Tampala as a Therapy for Vulvovaginal Candidiasis in Rattus Norvegicus - Qatrunnada Naqiyyah Khusmitha, Herdian Fitria Widyanto Putri, Dwi Yuni Nur Hidayati, Tri Yudani Mardining Raras (Pakistan Journal of Medical & Health Sciences, 2022)
Vulvovaginal candidiasis (VVC) is the second most prevalent form of vaginitis and is caused by Candida species, particularly Candida albicans. Bajakah Tampala is now being developed as an herbal medication due to the belief that it may heal a variety of diseases. This study aimed to determine the effect of Bajakah Tampala extract on vulvovaginal candidiasis in experimental model. This study measured the number of Candida albicans colonies, the number of neutrophil cells in the vaginal lumen of rats, and the levels of proinflammatory cytokines (TNF-α, IL-6) in rat blood serum to assess the efficacy of antifungal medication. Rats were separated into negative control, 10mg/kgBW Fluconazole, 427.5 mg, 451.3 mg, and 475 mg methanol extract of Bajakah Tampala groups. Fluconazole and Bajakah Tampala were able to decrease the amount of Candida albicans colonies, neutrophils, and serum TNF-α and IL-6 levels. According to the results of this study, Bajakah Tampala have the same antifungal potency as fluconazole. Keywords: Vulvovaginal candidiasis; Bajakah Tampala; fluconazole; Candida albicans; number of neutrophil colonies; TNF-α; IL-6